Etymology of Death from ancient, Modern and Islamic Perspectives - Dr Ayesha sabeen (International Research Journal of Arabic and Islamic Studies, 2023)
Death has become a strangely popular subject during the latter half of the 20th century. Before that time, perhaps rather surprisingly, it was a theme largely eschewed in serious scientific, and to a lesser extent, philosophical speculation. It was neglected in biological research, and being beyond the physician’s ministrations, was deemed largely irrelevant by medical practice. In modern times, however, the study of death has become a central concern in all these disciplines and in many others. So, death is defined in various perspectives.